Geospatial modeling of optimal zones for sustainable urbanization in southwestern NEOM, Saudi Arabia using geomatics techniques - Alogayell, Haya M.; Kamal, Ahmed; Alkadi, Ibtesam I.; Ramadan, Rasha H.; Ramadan, Mona S. (Frontiers in Built Environment, 2024)
Our study meticulously pursued its objectives through a strategic data-gathering approach and a thorough analytical evaluation. In the data collection phase, we undertook an exhaustive accumulation of geographical and environmental information, utilizing high-resolution satellite images and diverse thematic maps. We employed GIS-based models and the Analytical Hierarchy Process (AHP) to effectively determine the most suitable areas for urban development. These models pinpointed zones along the coastal areas and nearby plains, spanning 198.89 square kilometers or 8.25% of the total study area, as highly appropriate for development due to their potential for desalination and tourism, and proximity to vital infrastructure such as the forthcoming NEOM airport and high-speed railway connections. The findings from the Southwestern NEOM model corroborate with NEOM's strategic goals, especially validating the chosen location for The Line. This location is considered ideal due to its accessibility, terrain suitability, and capability to incorporate renewable energy and sustainable water management, thereby supporting the strategic aims and placement of the initiative. This not only highlights the strategic positioning of these areas but also aligns with the Saudi Vision 2030, fostering economic diversification and sustainable development. Together, these actions have established a comprehensive framework for urban planning that respects environmental conservation and promotes sustainable development objectives. By incorporating socio-economic and cultural factors, our research offers a well-rounded approach to urban development, ensuring that new infrastructure is both environmentally considerate and strategically situated to promote enduring growth and community wellbeing in Southwestern NEOM.